Christmas on 4th Street [large type] : a fool's gold romance - Mallery, Susan (Mallery, Susan. Fool's gold., 2013)
Noelle Perkins just got a second chance at life, and she intends to make the most of every minute. That's why she ditched a frustrating legal career to open her own store in Fool's Gold, California. The Christmas Attic celebrates everything that's magical about her favorite season. Business is booming, and as a bonus, gorgeous army doctor Gabriel Boylan, at home while recuperating from an injury, has offered to help out during the holiday rush.